Designing mindfulness information for interaction in social media: The role of information framing, health risk perception and lay theories of health - Wang, Xiaomei; Zhu, Bin; Guo, Qing; Wang, Wenyu; Zhao, Ruoxuan (Frontiers in Psychology, 2023)
The purpose of this study is to assess the impact of information design based on the gain and loss framework on people's willingness to interact with mindfulness information, and to identify the framework for achieving better results. We find that information design based on the framework of gains and losses can enhance the positive effect of communication. Specifically, the individuals are more willing to interact mindfulness information when they are exposed to gain-framed information rather than loss-framed. The findings of the first experiment shows gain framing has a direct advantage effect on the communication effect. While in the second experiment, we find that loss framing, compared with gain framing, led to greater health risk perception. In turn, participants are more likely to interact with mindfulness information with others. Additionally, our results show that the lay theories of health plays a moderating role in the direct effect of information framework on willingness to interact with mindfulness information in social media. When individuals hold incremental lay theories, they are more willing to interact with mindfulness information under the gain-framed information condition compared with the loss-framed information condition. However, when individuals were in entity condition, there is no significant difference in the willingness to interact with mindfulness information between the gain-framed and loss-framed information. Our studies of integrating information framework into designing mindfulness information suggest a promising strategy of health information interaction in social media.